2012
DOI: 10.1111/j.1751-1097.2012.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Optical Properties of Dissolved Humic Substances by their Molecular Complexity

Abstract: In this study, we show that several UV-Vis absorbance, steady-state and time-resolved fluorescence parameters of a series of dissolved humic substances (DHS) from different sources (e.g. terrestrial fulvic and humic acids, and humic acid-like molecules extracted from composted and vermicomposted wastes) correlate with the molar absorptivity at 280 nm per mole of organic carbon (ε(280)), which in turn is proportional to the molecular complexity (e.g. molecular size, aromaticity and oxidation degree) of the DHS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
(134 reference statements)
1
22
0
Order By: Relevance
“…In addition, Wang and Zhang recently reported that presence of energy transfer from polycyclic aromatic hydrocarbons to FDOM occurs because of the significant overlap between the emission spectra of polycyclic aromatic hydrocarbons and absorbance spectra of FDOM (Wang and Zhang, 2014). In fact, the humic substances themselves can also present intermolecular energy transfer between their electron donor groups (e.g., indoles, polyhydroxylated aromatics) and acceptor groups (e.g., oxidized aromatics and quinones) (Boyle et al, 2009;Del Vecchio and Blough, 2004); and the extent of the intermolecular energy transfer seemed to increase with increasing molecular complexity of the humic substances (Mignone et al, 2012).…”
Section: 1mentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, Wang and Zhang recently reported that presence of energy transfer from polycyclic aromatic hydrocarbons to FDOM occurs because of the significant overlap between the emission spectra of polycyclic aromatic hydrocarbons and absorbance spectra of FDOM (Wang and Zhang, 2014). In fact, the humic substances themselves can also present intermolecular energy transfer between their electron donor groups (e.g., indoles, polyhydroxylated aromatics) and acceptor groups (e.g., oxidized aromatics and quinones) (Boyle et al, 2009;Del Vecchio and Blough, 2004); and the extent of the intermolecular energy transfer seemed to increase with increasing molecular complexity of the humic substances (Mignone et al, 2012).…”
Section: 1mentioning
confidence: 96%
“…Rayleigh light scattering was eliminated using a 290 nm emission cutoff filter. Prior to measuring, highly concentrated samples were diluted with Milli-Q water to achieve absorbance values of less than 0.1 cm À1 at 254 nm, which meets the requirement for eliminating inner-filter effects during fluorescence measurements (Miller et al, 2010). According to the manufacturer's suggested protocols, the spectrophotometer was corrected for excitation and emission.…”
Section: Fluorescence Measurements and Parafac Modelingmentioning
confidence: 99%
“…Indeed, the latter can potentially form supramolecular assemblies based on intramolecular energy transfer requiring small donor to acceptor distances (Jørgensen et al, 2011;Cuss and Guéguen, 2015;Wang et al, 2015). Moreover, the increasing molecular complexity of humic substances increases the intermolecular energy transfer with other fluorescent components like tyrosine-like compound (Mignone et al, 2012).…”
Section: Terrestrial Inputs Of Cdommentioning
confidence: 99%
“…DOM can also bind with trace contaminants 19, 51 and heavy metals 32 by forming molecular aggregates, altering the behavior, mobility and transport of these compounds. Nevertheless, the intermolecular energy transfer depends on the molecular complexity of the humic substance 52 . For example, the humic-like and protein-like components are expected to have different capacities to bind with trace contaminants or heavy metals.…”
Section: Resultsmentioning
confidence: 99%